I was rolling along just fine in my logic class until we got to conditional proofs. I understand the rules on their own. I understand where I'm starting and where I need to go; but when I look at the premises, for some reason I cannot see the path to get me to my conclusion. I will be posting homework help in the homework forum. I would appreciate any help.

I guess I can't post anywhere else yet. Can someone please help me.

1. ~KvL Premise
2. K->(L->M) /KvM Premise

When I look at this, I immediately think that I should assume K. Which then gives me (L->M) by MP. Then if I nest the other conditional, I would assume L which gives me M by MP. But then I have K->M which is not what I need when I use Imp because it gives me ~KvM. Help!

I was rolling along just fine in my logic class until we got to conditional proofs. I understand the rules on their own. I understand where I'm starting and where I need to go; but when I look at the premises, for some reason I cannot see the path to get me to my conclusion. I will be posting homework help in the homework forum. I would appreciate any help.

I guess I can't post anywhere else yet. Can someone please help me.

1. ~KvL Premise
2. K->(L->M) /KvM Premise

When I look at this, I immediately think that I should assume K. Which then gives me (L->M) by MP. Then if I nest the other conditional, I would assume L which gives me M by MP. But then I have K->M which is not what I need when I use Imp because it gives me ~KvM. Help!

~KvM
K (Assumption)
M (DS)
MvK (Addition)
KvM (Commutation)

I was rolling along just fine in my logic class until we got to conditional proofs. I understand the rules on their own. I understand where I'm starting and where I need to go; but when I look at the premises, for some reason I cannot see the path to get me to my conclusion. I will be posting homework help in the homework forum. I would appreciate any help.

I guess I can't post anywhere else yet. Can someone please help me.

1. ~KvL Premise
2. K->(L->M) /KvM Premise

When I look at this, I immediately think that I should assume K. Which then gives me (L->M) by MP. Then if I nest the other conditional, I would assume L which gives me M by MP. But then I have K->M which is not what I need when I use Imp because it gives me ~KvM. Help!

It's not clear from this what it is you are trying to prove. Is it supposed to be ~KvL, K->(L->M) |- KvM ? This isn't a valid argument. Counterexample:
K = F
L = F
M = F

It's not clear from this what it is you are trying to prove. Is it supposed to be ~KvL, K->(L->M) |- KvM ? This isn't a valid argument. Counterexample:
K = F
L = F
M = F

The values you assign give us true premises and a true conclusion. So why isn't the argument valid?

The values you assign give us true premises and a true conclusion. So why isn't the argument valid?

If the argument you are trying to prove is indeed:

~KvL, K->(L->M) |- KvM

And as you didn't state otherwise, I assume it is, then my counterexample is correct. (KvM) is false if and only if both K and M are false, the truth table for the disjunction looks like this:

If the argument you are trying to prove is indeed:

~KvL, K->(L->M) |- KvM

And as you didn't state otherwise, I assume it is, then my counterexample is correct. (KvM) is false if and only if both K and M are false, the truth table for the disjunction looks like this:

So if K is false, then ~K is true, and ~KvM, is true.